2020
DOI: 10.1590/1980-57642020dn14-040005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of early cognitive indicators in mild cognitive impairment

Abstract: The aging of the population leads to an increase in the prevalence of dementia and mild cognitive impairment (MCI). Alzheimer's disease (AD) is the most common cause of dementia. Recent studies highlight the early non-amnestic deficits in AD and MCI. The European Union report shows the importance of thoroughly assessing cognitive aspects that have been poorly evaluated, such as processing speed (PS), which could represent early indicators of cognitive decline. Objective: To analyze the diagnostic accuracy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…There is also evidence of a correlation between reductions in processing speed and general cognitive performance. 18 It is interesting to note that a reduction in processing speed is also related to subjective memory complaints 43 . Although this kind of complaint usually does not involve an objective deficit in standard tests, it is possible that patients somehow already perceive their slower reaction time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence of a correlation between reductions in processing speed and general cognitive performance. 18 It is interesting to note that a reduction in processing speed is also related to subjective memory complaints 43 . Although this kind of complaint usually does not involve an objective deficit in standard tests, it is possible that patients somehow already perceive their slower reaction time.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, processing speed has been seen as a fundamental aspect of cognition and an essential aspect of healthy aging 17 . Studies have shown that it declines through many neurodegenerative conditions 13,15,16,[18][19][20] . One metanalysis found slower reaction time among MCI patients than among healthily aging individuals 21 .…”
Section: Introductionmentioning
confidence: 99%
“… 25 , 30 Analyses comparing medical diagnosis to the assessment of processing speed measures reached similar results. 31 Therefore, there is still room for discussion on how to detect MCI, especially considering its heterogeneity and considering the different contexts seen in LMIC and HIC.…”
Section: Diagnosismentioning
confidence: 99%
“…In the latter, neuropsychological assessment is a more accessible course of action, 12 even in the initial stages. 31 Activities of daily living scales are already used in clinical contexts, but a closer look at errors and their awareness could suggest the onset of a pathological process in the very beginning and be a useful approach to MCI screening.…”
Section: State Of the Art And Proposalmentioning
confidence: 99%
“…But to keep up with the technological advances of healthcare and cognitive neuroscience, in general, more efforts must be made in the field of clinical neuropsychology to develop and validate new and more technology-based instruments considering variables known to be valuable and that technology made it possible to use such as processing speed and reaction time. 17 The paper and pencil neuropsychological tests hardly have precise reaction time measurements, but this is an advantage that stands out among computerized tests: specific and complex variables, such as reaction time, can be measured even in milliseconds. 18 Reaction time is a variable that seems to be affected throughout many types of neurodegenerative conditions, 19 - 22 and the present computerized battery focuses on the reaction time as its primary measure — although it is also able to measure errors.…”
Section: Introductionmentioning
confidence: 99%